2002
DOI: 10.1159/000052057
|View full text |Cite
|
Sign up to set email alerts
|

Sweden: Integrated Compulsory Treatment

Abstract: In the year 2000, 804 adults were in coercive care for a maximum of 6 months under the Swedish Act on Care of Addicts in Certain Cases, which has both paternalistic and utilitarian motives. The extensive rights of the state to intervene in the private lives of its citizens seem to have a solid support in society. The article describes the present system and offers some explanations for its acceptance by looking at history. The fact that compulsory decisions have been made within the social administration has m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 3 publications
0
20
0
3
Order By: Relevance
“…However, and intriguingly enough, he has shown that what is not present in a language is likely to be something that the speakers in that culture may not have been obliged to think about to a great extent. In the case of the Nordic countries, for instance, historically there has not been a need to rely on a formulation in terms of a disease of the individual will to provide a justification for society and the state to act upon social alcohol and drug problems (Palm & Stenius, 2002). Although the Anglo-American concept of addiction has made a prominent entry into popular lay speech in recent years in Finland, for example (Hellman, 2010), a comparison between popular media narratives in the United States and in Finland still shows rather crucial differences in how the addiction phenomenon is conceptualized in the two societies (Hellman & Room, 2014).…”
Section: Is There a Common Concept Across Languages?mentioning
confidence: 99%
“…However, and intriguingly enough, he has shown that what is not present in a language is likely to be something that the speakers in that culture may not have been obliged to think about to a great extent. In the case of the Nordic countries, for instance, historically there has not been a need to rely on a formulation in terms of a disease of the individual will to provide a justification for society and the state to act upon social alcohol and drug problems (Palm & Stenius, 2002). Although the Anglo-American concept of addiction has made a prominent entry into popular lay speech in recent years in Finland, for example (Hellman, 2010), a comparison between popular media narratives in the United States and in Finland still shows rather crucial differences in how the addiction phenomenon is conceptualized in the two societies (Hellman & Room, 2014).…”
Section: Is There a Common Concept Across Languages?mentioning
confidence: 99%
“…In Sweden, the main responsibility for providing regular substance misuse treatment -compulsory, as well as on voluntary basis -lies with social services at the municipal level [28] . The municipalities offer social assistance, finance residential treatment homes which mainly focus on nonmedical treatment and have close co-operation with the healthcare organization at specialized clinics.…”
Section: Settingmentioning
confidence: 99%
“…In short, a substance abuser who endangers his/her own or others’ health, or risks damaging his/her own life, and who does not enter treatment by his/her own decision shall be court ordered to treatment for a maximum period of 6 months (cf. Palm & Stenius, 2002). The treatment is carried out at specialised LVM‐institutions with the aim of stopping substance abuse, providing motivation to continue with voluntary treatment and promoting long‐term rehabilitation (SOU, 1987).…”
Section: Introductionmentioning
confidence: 99%